2022
DOI: 10.1111/jmcb.12992
|View full text |Cite
|
Sign up to set email alerts
|

Money, Bitcoin, and Monetary Policy

Abstract: A search‐theoretic model is constructed, where money and Bitcoin can be used as mediums of exchange. We investigate how each currency facilitates transactions and how they compete with each other. Quantitative analysis shows that welfare in an economy with both money and Bitcoin is lower than in a money‐only economy due to congestions in the confirmation of Bitcoin transactions and that the welfare gap between the two economies expands as inflation rises. Moreover, an increase in transaction fees for Bitcoin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…( 2017 ) argued that Bitcoin is subject to the same economic factors as traditional fiat currencies, and is not entirely unaffected by government policies. Kang and Lee ( 2022 ) constructed a search-theoretic model to investigate how conventional money and Bitcoin facilitate transactions and concluded that benefits in an economy with both is lower than in a money-only economy due to surcharges in the confirmation of Bitcoin transactions. From an empirical viewpoint, Aharon et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…( 2017 ) argued that Bitcoin is subject to the same economic factors as traditional fiat currencies, and is not entirely unaffected by government policies. Kang and Lee ( 2022 ) constructed a search-theoretic model to investigate how conventional money and Bitcoin facilitate transactions and concluded that benefits in an economy with both is lower than in a money-only economy due to surcharges in the confirmation of Bitcoin transactions. From an empirical viewpoint, Aharon et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chiu and Koeppl (2022b) and Kang (2023) investigate double spending incentives in the Bitcoin system, and Choi and Rocheteau (2021) and Pagnotta (2022) study cryptocurrency pricing. Fernández‐Villaverde and Sanches (2019), Schilling and Uhlig (2019), and Kang and Lee (forthcoming) explore the macroeconomic implications of cryptocurrencies via currency competition. While these papers focus on analyzing the economic implications of technical features of digital currency, such as blockchain technology, we focus on the privacy issue of digital currency payments 3…”
Section: Introductionmentioning
confidence: 99%